Geographic Distribution of Childbirth among Adolescents in Cameroon from 2003 to 2005 - P. M. Tebeu; J. D. Kemfang; D. I. Sandjong; E. Kongnyuy; G. Halle; A. S. Doh (Obstetrics and Gynecology International)
Objective. To determine the frequency and the trend of adolescents (10–19 years) in childbirth within a period of 3 years in referral maternity units in Cameroon. Method. Descriptive and retrospective study for a 3-year period (2003–2005) in referral maternity units headed by a qualified Obstetrician-Gynecologist. We analyzed the trend and geographic distribution of 8222 adolescent deliveries over 3 years. Epi Info 3.5 software was used for data analysis. Chi square test for trend was used to assess the contribution of adolescent deliveries over years. The trend was considered significant if P<.05. Results. During the period of the study, there was a total of 8387 deliveries. We excluded 165 women because of lack of information about age. We therefore included a total of 8222 adolescent deliveries. Overall, the contribution of adolescents to deliveries ranged from 6.87% to 26.51%, depending on the region with a national mean of 14.23%. Adolescents aged 16 or less contributed to 2.82% of deliveries while those aged from 17 to 19 contributed to 11.41%. The contribution of adolescents to deliveries decreased significantly over 3 years (P<.0001). Conclusion. The study underscores the importance of Public Health programs in strengthening maternity services for adolescents in Cameroon while taking into consideration geographic differences.